2007
DOI: 10.1007/s10517-007-0271-z
|View full text |Cite
|
Sign up to set email alerts
|

Cultures of hESM human embryonic stem cells: Chromosomal aberrations and karyotype stability

Abstract: Cytogenetic analysis of karyotypes of hESM01-hESM04 human embryonic stem cells and substrains derived from these strains showed that all these strains retained normal karyotype during long-term culturing. Two substrains of embryonic stem cells with chromosome aberrations indicating clonal origin of these strains were detected. The potentialities of using analysis of chromosome variability of embryonic stem cells for evaluation of predisposition of the corresponding genotypes to the formation of chromosome abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Chromosomal rearra ngements in hESM0309 cell line Using DAPI staining, it was shown previously that in all cells of hESM0309 cell line chromosomes 4 and 9 were rearranged [5]. The patterns revealed by the staining allowed to assume that chromosome 4 contained a partial deletion and chromosome 9 a partial duplication.…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…Chromosomal rearra ngements in hESM0309 cell line Using DAPI staining, it was shown previously that in all cells of hESM0309 cell line chromosomes 4 and 9 were rearranged [5]. The patterns revealed by the staining allowed to assume that chromosome 4 contained a partial deletion and chromosome 9 a partial duplication.…”
Section: Resultsmentioning
confidence: 84%
“…Karyotyping of hESM01r18 and hESM0309 cell lines demonstrated that chromosomes r(18) and dup (9), respectively, were present in all cells from given cell lines [5]. hESM01r18 and hESM0309 cells showed a higher proliferation rate and more robust cultivation conditions compared with their parental cell lines.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations